Melioidosis (KYAMC Journal, 2017)
Melioidosis is an important disease caused by a Gram-negative bacterium, Burkholderia pseudomallei. The true incidence of melioidosis is unknown for most countries of the world including Bangladesh. Due to its increasing incidence in many countries of the world it is an important issue now days. Due to variability of clinical features and limited availability of laboratory facilities the disease remains largely under-reported.Early and specific diagnosis is important to ensure a favourable outcome regarding this disease. In this paper history, transmission, sign symptoms, diagnosis and prevention of melioidosis are critically reviewed to know about something regarding this diseaseKYAMC Journal Vol. 4, No.-1, July 2013, Page 353-356